Pola Preferensi Politik Pemilih Pemula Di Kota Makassar - Ekawaty, Dian; Saharuddin; Pardi; Syarif, Muhammad Zacky Athaya (Palita: Journal of Social Religion Research, 2024)
First-time voters are a fairly large segment of voters. This shows that First-Time voters are a large resource in politics in Indonesia. Indonesia as a democratic country certainly expects every element of society to be actively involved in every democratic process, including the first-time voter segment. First-time voters as an important segment then have quite good political awareness. Through this political awareness, a pattern of political preference formation will then be formed. First-time voters as a large political resource are of course highly expected to be able to participate, at least voting in elections. So far, existing research regarding First-time voters only places as mere objects. However, this research then examines in more depth the patterns of political preference formation that will influence the political behavior of first-time voters. This research is qualitative research with primary data obtained through in-depth interviews with high school students as research informants. Based on the research conducted, it appears that First-time voters in Makassar City have quite good political awareness, which is an implication of their better political knowledge. So, when making choices in an election, First-time voters have a tendency to make their own choices based on their political preferences. The pattern of forming political preferences of first-time voters is sociology, rationality and psychology. Keywords: Firs-time voters, Political Preferences, Political Awareness